2004
DOI: 10.1590/s0041-87812004000500009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nephrotic state on the infectious profile in childhood idiopathic nephrotic syndrome

Abstract: Patients with idiopathic nephrotic syndrome present alterations in their cellular and humoral immune reactions that predispose them to the development of infectious processes.PURPOSE: To characterize the infectious processes in patients with idiopathic nephrotic syndrome. PATIENTS AND METHODS: Ninety-two children and adolescents with idiopathic nephrotic syndrome were assessed retrospectively. The types of infection were grouped as follows: upper respiratory tract infections; pneumonia; skin infections; perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 12 publications
3
20
0
1
Order By: Relevance
“…Two studies from India & Nigeria found it as the most common infection and two studies from Pakistan & Taiwan found it as the 2 nd most common infection 1,8,[10][11] . Organisms causing UTI were almost similar to other studies though one study found staphylococcus aureus as the commonest organism 1,[9][10][11] . We found only one case of Tuberculosis.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Two studies from India & Nigeria found it as the most common infection and two studies from Pakistan & Taiwan found it as the 2 nd most common infection 1,8,[10][11] . Organisms causing UTI were almost similar to other studies though one study found staphylococcus aureus as the commonest organism 1,[9][10][11] . We found only one case of Tuberculosis.…”
Section: Discussionsupporting
confidence: 74%
“…A recent study in Pakistan showed that ARI was the commonest infection in children with newly diagnosed primary nephrotic syndrome. 1 Three studies from Iran, Taiwan & Brazil also found similar result [7][8][9] . One study from India found it as the 3 rd most common infection 10 .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…ascites as a potential culture medium and defective cell mediated immunitiy is responsible for increased incidence of infections in nephrotic syndrome. 7,8 Younger age, severe clinical types of nephrotic syndrome with severe ascites, use of cytotoxic drugs compared to prednisolone therapy alone and the presence of nephrotic range proteinuria itself have been identified as risk factors for the infections, whereas serum cholesterol more than 400 mg/dl and hypoalbuminemia less than 1.5 gm/dl is specifically identified for spontaneous bacterial peritonitis. 4,6,7,9,10 In children with nephrotic syndrome organism frequently encountered in infection are pneumococci, haemophilus influenze, beta haemolytic streptococci and gram negative bacteria.…”
Section: Introductionmentioning
confidence: 99%